Perbedaan Pemberian Pengaruh Pemberian MWD, Us, Latihan Eksentrik Quadriceps dengan MWD, Us, Latihan Statik Isometrik Quadriceps Terhadap Peningkatan Kekuatan Otot Quadriceps pada Tendinitis Patelaris (Fisioterapi : Jurnal Ilmiah Fisioterapi, 2009)
This research aims to detect intervention gift influence difference mwd, us and eccentric practice quadriceps with intervention mwd, us and practice statik isometric quadriceps towards muscle strength enhanced quadriceps in condition tendinitis patelaris. this research is done at physiotherapy clinic indonusa one superior that during 1 month in Juli-Agustus 2008, with sample total consists of 14 person. Research gets result that gift mwd, us and eccentric practice quadriceps gives muscle strength enhanced qua-driceps more have a meaning compared with gift mwd, us and practice statik isometric quadriceps in condition tendinitis patelaris. Research concludes that my treatment group very is suggested in condition tendinitis patelaris to increase muscle strength quadriceps.keywords: Muscle Strength Quadriceps, Eccentric Practice, Isometric